PENGEMBANGAN MEDIA CERITA BERGAMBAR INTERAKTIF BERMUATAN MITIGASI BENCANA UNTUK MENINGKATKAN KEMAMPUAN BERBAHASA LISAN ANAK USIA DINI - Utama, Windi Wulandari Iman (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Oral language skills in early childhood play a crucial role in children's cognitive, social, and emotional development. This study aims to develop an innovative, child-centered picture story media closely related to the early childhood environment. The research focuses on developing picture story media incorporating disaster mitigation content to enhance oral language skills in young children. The research method used is Research and Development (RnD) with the ADDIE model. For the feasibility test, the study involved seven experts: two early childhood education (ECE) content experts, two environmental content experts, two media experts, and one language expert. The research sample consisted of 137 children, including 19 children in the small group trial, 95 children in the large group trial, and 23 children in the effectiveness test. The findings reveal that: (1) based on the preliminary study, children's oral language skills need improvement; (2) teachers require the development of instructional media applicable to enhancing oral language skills in early childhood; (3) the development of picture story media follows the ADDIE instructional media development model; (4) the picture story media model is suitable for enhancing oral language skills in early childhood; and (5) interactive picture story media is effective in improving children's oral language skills, as they demonstrate significant progress in pronunciation, vocabulary expansion, sentence formation, and self-expression. Through the integration of disaster mitigation content in interactive picture story media, strategies to improve oral language skills in early childhood become more diverse and contribute to raising children's awareness of their immediate environmental characteristics.